Projecting Possibilities in the Nominal Domain: Spanish Uno Cualquiera. (8th December 2017) - Alonso-Ovalle, Luis; Menéndez-Benito, Paula
Abstract: Recent research argues that modal verbs project their domain of quantification from a part of the evaluation world—their 'modal anchor' (Hacquard 2006, 2009 ; Arregui 2009 ; Kratzer 2009, 2013, 2015 ). Based on the behaviour of the Spanish modal indefinite uno cualquiera, we contend that modal nominals can do the same. Uno cualquiera contributes modality: Juan cogió una carta cualquiera ('Juan picked a random card') conveys that Juan picked a card and that he chose it indiscriminately—he could have picked any other card. This 'random choice' interpretation is ruled out with non-volitional predicates (Choi & Romero 2008 ) and when uno cualquiera is in the subject position of agentive verbs. When uno cualquiera is embedded under some modals, another possibility arises: uno cualquiera introduces a distribution effect with respect to the worlds that the modal ranges over. For instance, ¡Coge una carta cualquiera! ('Take any card!') can be interpreted as conveying that any card is a permitted option. However, this harmonic interpretation is not available with all kinds of modals. We claim that this pattern can be derived if uno cualquiera is a nominal quantifier with a modal component that is anchored to an event. On this proposal, different interpretations arise depending on what event uno cualquiera takes as anchor. We argue that random choice modality is linked to the decision taken by the agent of the event described by the sentence. When the anchor of uno cualquiera is the event argument of the verb, uno cualquiera can access the decision that triggered this event, yielding the random choice interpretation. The selectional constraints that uno cualquiera imposes on its anchor restrict the types of modals that allow for harmonic interpretations.